KELAYAKAN PENGEMBANGAN MULTIMEDIA INTERAKTIF RAMAH ANAK UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP DAN KARAKTER CINTA TANAH AIR SISWA KELAS IV SD - Melani Septi Arista Anggraini; E. Kus Eddy Sartono (Balai Besar Guru Penggerak Jawa Timur, 2019)
The purpose of the research was to produce development of child-friendly interactive multimedia to improve the understanding of the concept and character of loving the country for fourth grade of elementary school student feasibility. The type of research that already done conducted is Research and Development through 10 stapes, 1) research and information collecting; 2) planning; 3) develop preliminary form of product; 4) preliminary field testing; 5) main product revision; 6) main field testing; 7) operasional product revision; 8) operational field testing; 9) final product revision; and 10) implementation and dissemination. The results of the research conducted show that the development of child friendly interactive multimedia products to improve the understanding of the concept and character of homeland love for grade IV elementary school students is